PENERAPAN MODEL MAKE A MATCH DENGAN MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR SUBTEMA AKU DAN CITA-CITAKU KELAS IV SDN TALUN 02 PATI - Ardyaningsih, Fitri; Fathurohman, Irfai; Purbasari, Imaniar (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the improvement of the learning outcomes of the sub-theme of Me and My Citizen through the application of the Make A Match Model with Media Puzzle to Grade IV students of SDN Talun 02 Pati. The results of the study on the learning outcomes of students' knowledge competence in the first cycle showed a load of Indonesian Language of 15 students achieving classical completeness of 68% with high qualifications. Social studies with 18 students achieve classical completeness of 82% with high qualifications. The learning outcomes of the knowledge aspects of the second cycle show that the contents of the Indonesian Language of 22 students achieved classical completeness of 100% with high qualifications. The social studies content of 21 students achieved classical completeness of 95%. Based on the results of classroom action research it can be concluded that the application of the Make A Match Model with Media Puzzle can improve the learning outcomes of the Sub-theme of Me and My Cita in Class IV SDN Talun 02 Pati.